Risk and Return Characteristics of Venture Capital-Backed Entrepreneurial Companies - Korteweg, Arthur; Sorensen, Morten (Review of Financial Studies, 2010)
[Valuations of entrepreneurial companies are only observed occasionally, albeit more frequently for well-performing companies. Consequently, estimators of risk and return must correct for sample selection to obtain consistent estimates. We develop a general model of dynamic sample selection and estimate it using data from venture capital investments in entrepreneurial companies. Our selection correction leads to markedly lower intercepts and higher estimates of risks compared to previous studies. The methodology is generally applicable to estimating risk and return in illiquid markets with endogenous trading.]